FC 123: Baseline Characteristics of the Flow Trial Population: Kidney Outcomes Trial With Once-Weekly Semaglutide in People With Type 2 Diabetes and Chronic Kidney Disease. (3rd May 2022) - Perkovic, Vlado; Baeres, Florian; Bakris, George; Bosch-Traberg, Heidrun; Idorn, Thomas; Mahaffey, Kenneth; Mann, Johannes; Mersebach, Henriette; Rossing, Peter; Tuttle, Katherine; Pratley, Richard
Abstract: BACKGROUND AND AIMS: Chronic kidney disease (CKD) in type 2 diabetes (T2D) is the most common cause of kidney failure. Despite treatment advances, there is still a large unmet need to prevent CKD progression, which can increase the risk for cardiovascular (CV) disease and kidney failure. Glucagon-like peptide-1 receptor agonists (GLP-1RAs) have beneficial effects on glycaemic control and body weight. Some agents have also shown CV benefit and can be used in people with T2D regardless of CKD status (except in end-stage renal disease). CV outcomes trials have suggested that GLP-1RAs may have kidney-protective effects, reducing albuminuria and preserving estimated glomerular filtration rate (eGFR). FLOW (NCT03819153) is a dedicated kidney outcomes trial designed to evaluate the effect of the once-weekly (OW) GLP-1RA semaglutide on major kidney outcomes in subjects with T2D and CKD; we report the blinded baseline characteristics of the FLOW trial population. METHOD: FLOW is an ongoing randomized, double-blinded, multinational, phase 3b trial in which 3535 subjects with T2D with an eGFR ≥25–≤75 mL/min/1.73 m², and urine albumin-to-creatinine ratio (UACR) >100 to <5000 mg/g were randomly assigned 1:1 to OW semaglutide 1.0 mg or placebo, as add-on to standard-of-care (including maximum labelled/tolerated renin–angiotensin–aldosterone system inhibitors). The primary endpoint is the time to first occurrence of kidney failure (as measured by persistent eGFR <15 mL/min/1.73 m² or initiation of chronic dialysis or kidney transplantation); ≥50% persistent eGFR reduction compared with baseline; and kidney or CV death. RESULTS: Baseline characteristics from FLOW are shown in the Table 1 . Overall, mean eGFR at baseline was 47.0 mL/min/1.73 m 2 with 79.6% of subjects having an eGFR of <60 mL/min/1.73 m 2 . Median UACR at baseline was 567 mg/g, and 68.5% of subjects had macroalbuminuria (≥300 mg/g). According to Kidney Disease: Improving Global Outcomes categories, 24.8% of subjects were classified as high risk and 68.2% of subjects were classified as very high risk for CKD progression (Figure 1 ). CONCLUSION: The FLOW trial will evaluate the efficacy and safety of semaglutide on kidney outcomes in subjects with T2D and high risk of kidney disease progression, a group for which additional therapies are urgently required.